2022
DOI: 10.1590/1981-6723.14121
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the sensory profile of Paipa cheese, the Colombian ripened cheese with protected designation of origin

Diego Alejandro Benavides-Sánchez,
Carolina Pena-Serna

Abstract: Paipa cheese is the unique Colombian ripened cheese produced from raw milk that has a protected designation of origin (PDO); nonetheless, to date, the dairy product lacks a defined sensory profile, since no study has been previously performed. The aim of this study was to approach the definition of the sensory attributes of the Paipa cheeses that are produced within the PDO region in order to establish the organoleptic aspects of the PDO regulation. A trained panel of five members used the multidimensional app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Among the food samples positive for L. monocytogenes, fresh cheese showed a prevalence of 26.6% (8/30), but the bacteria were absent in all the mature cheeses (0/30). This level of prevalence in fresh cheeses (26.6%) might seem high compared with what has been published for various countries, at less than 9.3% [51][52][53][54][55][56][57], and a few studies have reported a higher prevalence range of 17.6 to 60% [45,47,58]. The variation in the prevalence of L. monocytogenes may be due to several factors.…”
Section: Discussionmentioning
confidence: 55%
“…Among the food samples positive for L. monocytogenes, fresh cheese showed a prevalence of 26.6% (8/30), but the bacteria were absent in all the mature cheeses (0/30). This level of prevalence in fresh cheeses (26.6%) might seem high compared with what has been published for various countries, at less than 9.3% [51][52][53][54][55][56][57], and a few studies have reported a higher prevalence range of 17.6 to 60% [45,47,58]. The variation in the prevalence of L. monocytogenes may be due to several factors.…”
Section: Discussionmentioning
confidence: 55%